The Phenomenon of Flame Jump in Counter–current Flame Propagation in Biomass Packed Beds – Experiments and Theory. Issue 6 (26th April 2022) - V M, Jaganathan; Ambatipudi, Mani Kalyani; S, Varunkumar
ABSTRACT: In this paper the phenomenon of flame jump vis-a-vis steady propagation in biomass packed beds in counter-current mode is discussed. By analyzing the fuel flux and propagation rate data from experiments with a range of oxidizers, namely, air, O2 -N2, O2 -CO2, and O2 -steam mixtures, parameter regimes of steady propagation, and flame jump are identified. A theoretical basis for this classification is developed by analyzing the thermo-chemical conversion of single particles subject to flow and thermal conditions in a packed bed. The ratio of the ignition ( t i g ) to devolatilization ( t v ) times is shown to emerge as the controlling parameter in determining the flame propagation regimes. It is found from the theoretical analysis that steady propagation occurs for t v / t i g < 2 and transition to flame jump occurs if t v / t i g > 2. Operational zones of a packed bed biomass system is mapped using the predicted ratio of t v / t i g as a function of volatiles-based equivalence ratio ( ϕ v ). Implications of these results to practical ligno-cellulosic biomass combustion and gasification systems, especially using oxygen-steam mixtures for hydrogen generation, are brought out.